(untitled) (Ameghiniana, 2013)
Type material of 39 bivalve taxa is here revised for the first time. In most cases type specimens were collected fossil or "subfossil" along the northeastem Argentine coastal area (Holocene; ca. 6,000-2,500 14C years B.P.). All of them are presently living on the shores of the western South Atlantic Ocean (Argentine Malacological Province). Data on the types and repositories, designation or reillustration of lectotypes and holotypes and synonyms are presented here as a result of a systematic revision based on new material. The taxonomic status of the different species is discussed, as well as their distribution and ecology.